Intensive neurorehabilitation and allogeneic stem cells transplantation in canine degenerative myelopathy - Gouveia, Débora; Correia, Jéssica; Cardoso, Ana; Carvalho, Carla; Oliveira, Ana Catarina; Almeida, António; Gamboa, Óscar; Ribeiro, Lénio; Branquinho, Mariana; Sousa, Ana; Lopes, Bruna; Sousa, Patrícia; et al. (Frontiers in Veterinary Science, 2023)
Degenerative myelopathy (DM) is a neurodegenerative spinal cord disease with upper motor neuron, progressive and chronic clinical signs, similar to amyotrophic lateral sclerosis (ALS). DM has a complex etiology manly associated to SOD1 gene mutation and its toxic role, with no specific treatment. Daily intensive rehabilitation showed survival time near 8 months but most animals are euthanized 6-12 months after clinical signs onset. This prospective controlled blinded cohort clinical study aims to evaluate neural regeneration response ability of DM dogs subjected to an intensive neurorehabilitation protocol with mesenchymal stem cells (MSCs) transplantation. 13 non-ambulatory (OFS 6 or 8) dogs with homozygous genotype DM/DM and diagnosed by exclusion were included. All were allocated to the intensive neurorehabilitation with MSCs protocol (INSCP) group (n=8) or to the ambulatory rehabilitation protocol (ARP) group (n=5), which differ in regard to training intensity, modalities frequency and MSCs transplantation. The INSCP group was hospitalized for 1 month (T0 to T1), followed by MSCs transplantation (T1) and a second month (T2), whereas the ARP group was under ambulatory treatment for the same 2 months. Survival mean time of total population was 375 days, with 438 days for the INSCP group and 274 for the ARP group, with marked difference on the Kaplan-Meier survival analysis. When comparing to the literature´s results there was also a clear difference by the one-sample t-test (p=0.013) with an increase in time of near 70%. OFS classifications between groups in each time point was significantly different (p=0.008) by the one-way ANOVA and the independent sample t-test. This INSCP showed to be safe, feasible and a possibility for a longer progression of DM dogs with quality of life and functional improvement. This study should be continued.